Rivaroxaban vs. warfarin for the treatment and prevention of venous thromboembolism: A meta-analysis - Liu, Zhuang; Song, Dan; Wang, Liang; Wang, Changfeng; Zhou, Jie; Sun, Jiali; Guo, Lei (Frontiers in Surgery, 2023)
Background Anticoagulant treatment is used to treat and prevent venous thromboembolism (VTE). However, the relative effectiveness of newer anticoagulants vs. warfarin has not been appraised. Objective The aim was to evaluate the safety and efficacy of rivaroxaban for VTE in comparison to warfarin. Materials and methods From January 2000 until October 2021, all related studies were collected by EMBASE, the Cochrane Library, PubMed and Web of Scienceand. During the review process, two reviewers independently analyzed the included studies, including quality evaluation, screening and data extraction. We focused on VTE events as our primary outcomes. Results In total, 20 trials were retrieved. These studies involved 230,320 patients, of which 74,018 received rivaroxaban and 156,302 received warfarin. Compared with warfarin, the incidence of VTE in rivaroxaban is significantly lower (risk ratio (RR) 0.71, 95% confidence interval (CI) [0.61, 0.84]; P < 0.0001, random effect model), and signiﬁcantly reduced major [RR: 0.84, 95% CI (0.77, 0.91); P < 0.0001, fixed effect model] and nonmajor [RR: 0.55, 95% CI (0.41, 0.74); P < 0.0001, fixed effect model] bleeding. No signiﬁcant differences in all-cause mortality between the two groups [RR: 0.68, 95% CI (0.45, 1.02); P = 0.06, fixed effect model]. Conclusion Rivaroxaban significantly reduced the incidence of VTE compared to warfarin in this meta-analysis. In order to verify these findings, larger sample sizes are required in well-designed studies.